2017
DOI: 10.18632/oncotarget.17309
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of pancreatic neuroendocrine carcinoma from pancreatic ductal adenocarcinoma using magnetic resonance imaging: The value of contrast-enhanced and diffusion weighted imaging

Abstract: Pancreatic neuroendocrine carcinoma (PNEC) is often misdiagnosed as pancreatic ductal adenocarcinoma (PDAC). This retrospective study differentiated PNEC from PDAC using magnetic resonance imaging (MRI), including contrast-enhanced (CE) and diffusion-weighted imaging (DWI). Clinical data and MRI findings, including the T1/T2 signal, tumor boundary, size, enhancement degree, and apparent diffusion coefficient (ADC), were compared between 37 PDACs and 13 PNECs. Boundaries were more poorly defined in PDAC than PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
2
14
0
1
Order By: Relevance
“…Pancreatic neuroendocrine carcinoma (PNEC) is a rare tumor that accounts for 2–3% of pancreatic neuroendocrine neoplasms (PNENs) [ 1 , 2 ]. Recently, several studies reported that PNEC usually showed hypovascular pattern in contrast-enhanced computed tomography (CT) or magnetic resonance imaging (MRI) [ 3 6 ]. In addition, ill-defined borders and lymph node invasion are also common in PNEC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pancreatic neuroendocrine carcinoma (PNEC) is a rare tumor that accounts for 2–3% of pancreatic neuroendocrine neoplasms (PNENs) [ 1 , 2 ]. Recently, several studies reported that PNEC usually showed hypovascular pattern in contrast-enhanced computed tomography (CT) or magnetic resonance imaging (MRI) [ 3 6 ]. In addition, ill-defined borders and lymph node invasion are also common in PNEC.…”
Section: Introductionmentioning
confidence: 99%
“…Overlaps in imaging findings between PNEC and PDAC have been reported previously [ 7 ]. In a prior study, we found that 57% of PNEC was misdiagnosed as PDAC [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous reports have investigated the correlation between imaging characteristics and the PNET grade. PNENs are generally enhanced in the early phase on contrast-enhanced CT and MRI ( 26 - 29 ), whereas low enhancement is observed in malignant PNENs ( 30 - 33 ). FDG-PET often reveals an FDG accumulation in cases of malignant or highly proliferative PNENs ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present most guidelines (ENETS, NANETS) recommend that MEN1 patients with small NF-PanNENs (≤2 cm), which are almost invariably asymptomatic, should be treated with a watch and wait policy [5, 12, 44, 47]. This policy evolved from findings that these small NF-PanNENs were not associated with increased mortality, the NF-PanNENs are multiple, that the patient cannot be cured of all NF-PanNEN lesions without a total pancreatectomy, and that most of these when followed show minimal growth [5, 11, 12, 79-81]. In the case of ZES in MEN1 patients a similar problem exists as the gastrinomas are in the duodenum in 80–90% of cases, they are invariably multiple, 50–70% are associated with local lymph node metastases, they are not curable without aggressive selection such as a Whipple resection, and long-term studies show unoperated patients with < 2–3 cm of imageable lesion have an excellent long-term survival, so it is generally recommend that this group also do not undergo routine resection [11-14, 47, 82, 83].…”
Section: Unmet Needs: Potential Specific Protocol Topicsmentioning
confidence: 99%